The Influence of Service Quality, Relationship Marketing, and Perceived Value on B2B Customer Satisfaction at PT Elkaka Putra Mandiri - Rahmat; Lukmanul Hakim; M. Hasan Ma'ruf (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the effect of job training, work communication, and work motivation on employee performance at PT Elkaka Putra Mandiri Lampung. This research employs a quantitative approach using a survey method involving all 31 employees as respondents through a saturated sampling technique. Data were collected using Likert-scale questionnaires and analyzed by multiple linear regression. The results show that job training has a negative and significant effect on employee performance, while work communication and work motivation have positive and significant effects. Simultaneously, all variables significantly influence employee performance, with work motivation identified as the most dominant factor. The findings highlight the importance of enhancing work motivation and communication effectiveness, as well as the need to evaluate training programs to better align with job requirements.   Keywords: Job Training, Work Communication, Work Motivation, Employee Performance